PELAKSANAAN PENDIDIKAN NONFORMAL DI LPKA BENTIRING PROVINSI BENGKULU - Jon Kenedi; Agus Zainal Ramat; Suardi Jasma (UNIB Press, Universitas Bengkulu, 2019)
This study aims to determine the implementation of Nonformal Education in LPKA in general. While in particular is describing whether there is an implementation of Non-formal Education in LPKA, describing the frequency of the implementation of Non-formal Education in LPKA and describing the driving factors and barriers to the implementation of Non-formal Education in LPKA. This study uses qualitative methods with descriptive data. Data analysis in this study using three methods, namely data reduction, data presentation, and Decision Making Verification. The results of this study indicate that: (1) Based on the findings of researchers in the field and existing theories, researchers concluded that the implementation of No formal Education in LPKA Benton Bengkulu Province already exists through the institution of a non-formal institution namely PKBM Ilmu Bunda with equality packages A, B and C , package B and C equality students have carried out the National Examination and Government institutions through the Provincial BLK (Training Center) which conducts training in sewing, automotive and making colek soaps to increase students' creativity while in LPKA. (2) Based on the findings of researchers in the field and existing theories, researchers can conclude that the frequency of Non-formal Education Implementation in LPKA is through PKBM Ilmu Bunda with the provisions of meeting schedules twice Thursday and Saturday, the duration of study is 60-90 minutes. Then the training specifically held by the Provincial BLK is scheduled to be erratic and has an influence on students, namely the fulfillment of the right to educate children and the independence of children to prepare the future of students after the prison period is over. (3) Based on the findings of researchers in the field and existing theories, researchers can conclude that the driving factor for the implementation of PNF in LPKA is that there is a concern for students, students have the right to get education and self-development (soft skills). Then the inhibiting factor for PNF implementation in LPKA is the building that is still with adult prisons, parents of students who have difficulty communicating and there are still students who are not cared for at all by the family. The solutions made by the LPKA to the barriers to package equality and training are: The LPKA party continues to carry out learning activities despite limited infrastructure and visits to the Provincial BLK, assisting students to meet parents to complete administration and strive for equality even though they are not managed by the family at all. Key Word : Nonformal Education, LPKA